2022
DOI: 10.1097/psy.0000000000001121
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Consumption, Psychiatric Diagnoses, and Pharmacotherapy 1 and 2 Years Before and After Newly Diagnosed HIV: A Case-Control Study Nested in The Greater Stockholm HIV Cohort Study

Abstract: Objective: We compare individuals with newly diagnosed HIV with sex-, age-, and socioeconomic status-matched HIV-negative controls, with the aim of studying the frequency of health care visits, the types of clinics visited, registered diagnoses, and psychopharmacotherapy. Methods: The data were collected through the Stockholm Region administrative database (Stockholm Regional Health Care Data Warehouse) for men and women (people) living with newly diagnosed HIV (PLWH) in their medical records (930 men, 450 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“… 3 This increased risk of contracting HIV has been reported among individuals with substance use disorder, 9 while Wandel et al showed that the prevalence of substance use disorders was high in HIV positive persons even before the diagnosis of HIV. 10 Risky behaviour can also occur in those who are disinhibited in certain affective disorders like mania. 11 On the other hand, having a chronic illness, such as HIV, can predispose to mental health disorders both from the development of AIDS and HIV-associated neurocognitive disorder (HAND) 10 as well as from various psychological and social processes such as stigma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 This increased risk of contracting HIV has been reported among individuals with substance use disorder, 9 while Wandel et al showed that the prevalence of substance use disorders was high in HIV positive persons even before the diagnosis of HIV. 10 Risky behaviour can also occur in those who are disinhibited in certain affective disorders like mania. 11 On the other hand, having a chronic illness, such as HIV, can predispose to mental health disorders both from the development of AIDS and HIV-associated neurocognitive disorder (HAND) 10 as well as from various psychological and social processes such as stigma.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Risky behaviour can also occur in those who are disinhibited in certain affective disorders like mania. 11 On the other hand, having a chronic illness, such as HIV, can predispose to mental health disorders both from the development of AIDS and HIV-associated neurocognitive disorder (HAND) 10 as well as from various psychological and social processes such as stigma. 12 In addition, antiretrovirals, 13 viral load 1 and decrease in functioning 1 can predispose to psychiatric morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Substance use disorders are also prevalent comorbidities that increase the risk of HIV acquisition and potentiate faster clinical HIV progression (29,30). Findings reported by Wändell et al (31) from the Greater Stockholm Cohort Study revealed that substance use disorders were elevated in PWH before the diagnosis of HIV. In addition, the elevated prevalence of substance use disorders persisted in the year after HIV diagnosis, which reflects the chronic and often relapsing nature of problematic substance use.…”
mentioning
confidence: 98%